Avian Influenza Virus Surveillance in South-Central Spain Using Fecal Samples of Aquatic Birds Foraging at Landfills - Bárbara, Andreia; Torrontegi, Olalla; Camacho, Maria-Cruz; Barral, Marta; Hernández, Jose-Manuel; Höfle, Ursula (Frontiers in Veterinary Science, 2017)
Aquatic wild birds have been intensively studied to better understand their role in avian influenza virus (AIV) maintenance and spread. To date, AIV surveillance has primarily focused on natural aquatic environments where different bird species aggregate and viral survival is enhanced. However, artificial habitats such as landfills are attracting substantial numbers of wild birds, AIV reservoir species included. The use of landfills as a predictable food source has significantly influenced population size, migratory traits and feeding behaviour of white storks (Ciconia ciconia) and black-headed gulls (Chroicocephalus ridibundus) among others. Considering the proximity of landfills to urban settlements and frequently poultry-farms, targeted monitoring of AIV in bird species that forage at landfills but are known to also frequent urban and agricultural habitats could be a useful means for monitoring of AIV, especially during periods of bird aggregation. During the wintering season 2014-2015 the prevalence of AIV in five avian species at two landfills in South-Central Spain was explored by rRT-PCR and species related temporal variation in AIV prevalence determined. We collected and tested 1186 fresh faecal samples from white storks (N=689), cattle egrets (Bubulcus ibis, N=116) and mixed flocks of gulls (N=381) as well as cloacal and oral swabs from five birds found dead. Seven samples contained AIV, five from gulls and one each from a stork and a cattle egret. Overall AIV prevalence was 0.60%. No significant temporal variation was observed in AIV prevalence. Prevalence differed significantly among the sampled taxonomic groups, being highest in gulls (1.31%). H16N3 subtype was detected from a cattle egret and H11N9 subtype from a white stork, whereas gulls harboured both subtypes in addition to H11N3 subtype. H16 subtype detection in a cattle egret evidences its host range may not be restricted to gulls. Our results indicate that wild birds foraging at landfills may carry different LPAIV subtypes.